Study of The Effect of Coal Quality Parameters on Gas Methane (CH4) Emission in Coal Fire for Sustainable Environment - Reni Arisanti; Maulana Yusuf; Muhammad Faizal (Research Centre of Inorganic Materials and Complexs, 2017)
Coal is formation media of Methane Gas which retains the ability to store gas in large quantities. Methane gas (CH4) one of the greenhouse gases that its existence can be troubling, because the gas can increase the impact of global warming, the can damage the ozone layer and increase the temperature of the earth. Methane gas (CH4) emissions that occur in the coal combustion process strongly influenced by the physical and chemical of coal. This research was intended to know how the influence of quality parameters and calorific value of coal methane gas (CH4) emission, and temperature in combustion process. This research is quantitative research with method of quantitative descriptive and descriptive associative approach. Average methane gas emissions (CH4) occurring for each calorific value of coal, calories 5900 kcal / kg 3.98 ppm, 6300 kcal / kg 1.30 ppm, 6700 kcal / kg 0.26 ppm, and 7600 kcal / kg 0.08 ppm. The relationship of temperature, calorific value and methane gas emission (CH4) the higher the calorific value, the required temperature will be greater and the gas emission is smaller, where the calories 5900 kcal / kg average temperature 63.75 oC, calories 6300 kcal / kg average 60,92 oC, calories 6700 kcal / kg average 52,59 oC, while for calorie 7600 kcal / kg average temperature 113,98 oC. Indonesian coal mostly consists low rank coal which can cause high methane (CH4) emissions that would also cause problems to the environment.